2009
DOI: 10.1080/08858190902854681
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Personal and/or Close Relationship Experience on Memorable Messages About Breast Cancer and the Perceived Speech Acts of the Sender

Abstract: Background-Memorable messages and their speech acts (purposes of the messages) can promote protection against breast cancer and guide health behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Using a control theory (Carver & Scheier, 1982, 1990Powers, 1973;Wiener, 1948) perspective, research has found that memorable messages help people understand and act in new or challenging situations via a negative feedback loop; these memorable messages are recalled when individuals self-assess their own behavior that violates or exceeds their goals and ideals (Ellis & Smith, 2004;, and they can help guide subsequent behavior to maintain personal standards. Research has demonstrated a range of memorable message types delivered under a variety of circumstances, such as college life (Nazione et al, 2011) organizational socialization (Stohl, 1986), faith and spirituality (Keeley, 2004), breast cancer (Smith, Atkin, Skubisz, Nazione, & Stohl, 2009), and aging (Holladay, 2002). Because this study seeks to uncover what messages are recalled by women serving community supervision, we ask: RQ1: What types of memorable messages do women on probation and parole report from their supervising agents?…”
Section: Influence Of Memorable Messages On Female Offenders As Suggementioning
confidence: 98%
“…Using a control theory (Carver & Scheier, 1982, 1990Powers, 1973;Wiener, 1948) perspective, research has found that memorable messages help people understand and act in new or challenging situations via a negative feedback loop; these memorable messages are recalled when individuals self-assess their own behavior that violates or exceeds their goals and ideals (Ellis & Smith, 2004;, and they can help guide subsequent behavior to maintain personal standards. Research has demonstrated a range of memorable message types delivered under a variety of circumstances, such as college life (Nazione et al, 2011) organizational socialization (Stohl, 1986), faith and spirituality (Keeley, 2004), breast cancer (Smith, Atkin, Skubisz, Nazione, & Stohl, 2009), and aging (Holladay, 2002). Because this study seeks to uncover what messages are recalled by women serving community supervision, we ask: RQ1: What types of memorable messages do women on probation and parole report from their supervising agents?…”
Section: Influence Of Memorable Messages On Female Offenders As Suggementioning
confidence: 98%
“…There have also been studies that have examined memorable messages about breast cancer. Smith, Atkin, Skubisz, Munday, and Stohl (2009) found that women who are the most likely to recall memorable breast cancer messages have had personal experience and close friends or relatives who have had experience with breast cancer. Other research by Smith et al (2009) has found that memorable breast cancer message topics include early detection, awareness, treatment, and prevention of breast cancer, and the most common sources of these messages are the media, friends, family, and medical professionals.…”
Section: Breast Cancermentioning
confidence: 99%
“…Smith, Atkin, Skubisz, Munday, and Stohl (2009) found that women who are the most likely to recall memorable breast cancer messages have had personal experience and close friends or relatives who have had experience with breast cancer. Other research by Smith et al (2009) has found that memorable breast cancer message topics include early detection, awareness, treatment, and prevention of breast cancer, and the most common sources of these messages are the media, friends, family, and medical professionals. They also examined the impact of different sources of messages on prevention or detection behaviors, and found that medical professionals were substantially more likely to influence breast cancer detection than breast cancer prevention behaviors.…”
Section: Breast Cancermentioning
confidence: 99%
“…In the last two and a half decades, communication scholars have studied memorable messages in terms of organizational socialization (e.g., Dallimore, 2003;Stohl, 1986), influence of family communication (e.g., Ellis & Smith, 2004;Medved, Brogan, McClanahan, Morris, & Shepherd, 2006), perceptions of illness and healthcare (e.g., Keely, 2004;Lauckner et al, 2012;Smith, Atkin, Skubisz, Nazion, & Stohl, 2009;Smith et al, 2010), constructions of identity (Heisler & Ellis, 2008;Holladay, 2002), and understandings of discrimination in an increasingly diverse world (Camara & Orbe, 2010). For this particular study, the literature on memorable messages represents a useful conceptual lens through which to study salient influences of current sexual practices (Medved et al, 2006).…”
Section: The Narratology Of Memorable Messages About Relationships Anmentioning
confidence: 99%